2003
DOI: 10.1071/ea02117
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting production of inoculum of the blackleg fungus (Leptosphaeria maculans) in south-eastern Australia

Abstract: The production of windborne ascospore inoculum of the blackleg fungus (Leptosphaeria maculans) was determined during 2000 and 2001 in 3 environments (Birchip, low rainfall; Wonwondah, medium rainfall; Lake Bolac, high rainfall) in Victoria. The weight of canola stubble (kg/ha) remaining on the soil surface in paddocks was estimated 6, 18, 30 and 42 months after harvest of the original canola crop. In all 3 environments only small amounts of stubble were present 18 months after harvest. Eighty percent of the 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
2
23
1
Order By: Relevance
“…Further research, in which the duration of wetness after each spray is estimated, would provide an indication of whether the total duration of wetness or the distribution of wetness periods influenced the rate of pseudothecium maturation. Nevertheless, the findings in the current study that interrupted wetness reduced the production of pseudothecia on stubble agree with earlier findings that the quantity of rainfall affected the quantity of ascospores released from stubble in Australia (Marcroft et al 2003). Marcroft et al (2003) reported that large numbers of ascospores were released from 6 month-old stubble collected from high rainfall areas whereas stubble from medium to low rainfall areas continued to release fewer ascospores for longer periods.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further research, in which the duration of wetness after each spray is estimated, would provide an indication of whether the total duration of wetness or the distribution of wetness periods influenced the rate of pseudothecium maturation. Nevertheless, the findings in the current study that interrupted wetness reduced the production of pseudothecia on stubble agree with earlier findings that the quantity of rainfall affected the quantity of ascospores released from stubble in Australia (Marcroft et al 2003). Marcroft et al (2003) reported that large numbers of ascospores were released from 6 month-old stubble collected from high rainfall areas whereas stubble from medium to low rainfall areas continued to release fewer ascospores for longer periods.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the findings in the current study that interrupted wetness reduced the production of pseudothecia on stubble agree with earlier findings that the quantity of rainfall affected the quantity of ascospores released from stubble in Australia (Marcroft et al 2003). Marcroft et al (2003) reported that large numbers of ascospores were released from 6 month-old stubble collected from high rainfall areas whereas stubble from medium to low rainfall areas continued to release fewer ascospores for longer periods. Similarly, in Saskatchewan, Canada, sporulation occurred earlier in the field as the frequency of moistening infested stubble between April and June increased (Petrie 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…L. maculans can survive and reproduce on even the most resistant lines (Marcroft et al, 2004). As quantitative resistance is partial, when L. maculans inoculum concentrations are high, it may not prevent large yield losses (Salisbury et al, 1995;Khangura and Barbetti, 2001;Marcroft et al, 2003).…”
Section: Quantitative Resistance In B Napusmentioning
confidence: 99%
“…Current methods to conduct this include the use of fungicides (Khangura & Barbetti 2004), burning of infected stubble and rotating cultivars containing different sources of resistance (Salisbury et al 1995). Marcroft et al (2003) recommend that new canola cultivars should be sown at a distance of at least 500 m from old stubble. The best method to prevent crop losses, however, has been the sowing of disease-resistant cultivars, which is based on the interaction of effector and resistance proteins of the pathogen and plant (See section 1.3.1).…”
Section: Disease Managementmentioning
confidence: 99%